Screening and determination for potential α‐glucosidase inhibitory constituents from Dalbergia odorifera T. Chen using ultrafiltration‐LC/ESI‐MSn. (1st July 2013) - Zhao, Chunfang; Liu, Yongqiang; Cong, Dengli; Zhang, Hui; Yu, Jiajia; Jiang, Ying; Cui, Xiuyue; Sun, Jiaming
ABSTRACT: In the present study, it was demonstrated that ethyl acetate soluble fraction partitioned from heartwood of Dalbergia odorifera T. Chen (HEF) had a remarkable inhibitory effect on α ‐glucosidase. Therefore HEF was selected as a starting material for screening the potential α ‐glucosidase inhibitors using ultrafiltration liquid chromatography/mass spectrometry (UF‐LC/MS). Twenty‐six compounds were identified with analysis of LC/MS. UF assay indicated that 18 compositions might be α ‐glucosidase inhibitors in HEF; eight of them were estimated for their α ‐glucosidase inhibitory activity, and the results showed that (2 S )‐liquiritigenin, (2 S )‐4′, 6‐dihydroxy‐ 7‐methoxyflavanone and isoliquiritigenin displayed obvious inhibition of yeast α ‐glucosidase. In addition, in order to control the quality of HEF, the content of five compounds in HEF was simultaneously determined for the first time. These results provide an important theoretical base for the further application of HEF to treat type 2 diabetes in the clinic and development of natural α ‐glucosidase inhibitors with low toxicity. Copyright © 2013 John Wiley & Sons, Ltd.